2022
DOI: 10.3390/ma15103488
|View full text |Cite
|
Sign up to set email alerts
|

Layered Perovskites BaM2In2O7 (M = La, Nd): From the Structure to the Ionic (O2−, H+) Conductivity

Abstract: The design of new oxide compounds that can be used as oxygen- or proton-conducting electrolytes for solid oxide fuel cells is actively in progress. Despite the intensive research activities regarding electrolytes with perovskite/fluorite structures, the search for other structural alternatives is of paramount importance. In this study we focus on a novel material with significantly improved properties for the electrochemical purposes. The two-layered BaNd2In2O7 perovskite with a Ruddlesden–Popper structure was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 46 publications
(34 reference statements)
1
2
0
Order By: Relevance
“…As reported in Tarasova et al’s work, , protonic conduction was evidenced for the parent La 2 BaIn 2 O 7 material under 400 °C. In the present work, to study the proton conduction properties of these acceptor-doped La 2 BaIn 2 O 7 materials, the electrical conductivities of the selected composition of La 1.7 Ba 1.3 In 2 O 6.85 were also recorded under the wet condition at high oxygen partial pressures, and the results are provided in Figure S3a–d.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…As reported in Tarasova et al’s work, , protonic conduction was evidenced for the parent La 2 BaIn 2 O 7 material under 400 °C. In the present work, to study the proton conduction properties of these acceptor-doped La 2 BaIn 2 O 7 materials, the electrical conductivities of the selected composition of La 1.7 Ba 1.3 In 2 O 6.85 were also recorded under the wet condition at high oxygen partial pressures, and the results are provided in Figure S3a–d.…”
Section: Resultssupporting
confidence: 75%
“…Then, numerous studies applying a doping strategy to further improve its oxide ion conductivity have been carried out by different research groups. As to the La 2 BaIn 2 O 7 material, the La 3+ and Ba 2+ cations also have ordered distributions in the rock salt layer and the perovskite layer, respectively, as shown in Figure d, due to the large ionic radius difference between La 3+ (1.216 Å) and Ba 2+ (1.47 Å) for CN = 9, and this material was reported even more early than NdBaInO 4 . However, until more recently, the protonic conduction was reported for the parent (La/Nd) 2 BaIn 2 O 7 materials by Tarasova et al , They claimed that the (La/Nd) 2 BaIn 2 O 7 materials demonstrated nearly pure protonic conductivity below 350 °C, and no obvious oxide ion conductions were observed.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 6 Temperature dependencies of conductivity under dry air for the compositions SrLa2ScInO7 (1), SrLa2Sc2O7 (2), BaLa2In2O7[41] (3), BaNd2In2O7[43] (4).…”
mentioning
confidence: 99%